The Influence Of Company Size, Profitability, And Tax Savings On The Capital Structure Of Pharmacy Companies Listed On The Indonesian Stock Exchange - Gregorius Paulus Tahu; Dewa Ayu Diah Pradnya Swari; I Wayan Widnyana (Jurnal Ilmu Sosial Mamangan, 2024)
Capital structure is a very important issue for companies because capital is one of the driving factors in a company to be able to carry out company operations. The size of a company can be measured by company size, the company's ability to make a profit is measured by profitability, apart from that, company tax savings can be measured by interest expenses by tax rates. The aim of this research is to determine the effect of company size, profitability and tax savings on the capital structure of Pharmaceutical Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The research object used in this research is the influence of company size, profitability and tax savings on the capital structure of pharmaceutical companies listed on the IDX for the 2019-2021 period. The sampling method in this research is to use techniquesnon probability sampling with methodpurposive sampling, where a sample of 36 observation data was obtained. Data analysis techniques use the Classic Assumption Test, Multiple Linear Regression Analysis, Determination Analysis, t Test, F Test. The results of this research show that company size has a positive and significant effect on the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange. Profitability has a negative and significant effect on the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange. Tax savings have a positive and significant effect on capital structure.